River and Lake Sailing Safety Management System - Doharman Lumban Tungkup (IWJ : Inland Waterways Journal, 2020)
Each ship has a safety management system in order to create a work environment that is safety-aware in operating and carrying out shipping. The safety of the voyage is not only seen from the condition of the ship, because many other factors influence it. One important factor is the implementation of a planned maintenance system (PMS) that can be carried out by operators or shipyards.